2015
DOI: 10.1007/s10459-015-9626-9
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare practitioners’ personal and professional values

Abstract: Personal and professional values of healthcare practitioners influence their clinical decisions. Understanding these values for individuals and across healthcare professions can help improve patient-centred decision-making by individual practitioners and interprofessional teams, respectively. We aimed to identify these values and integrate them into a single framework using Schwartz's values model. We searched Medline, Embase, PsycINFO, CINAHL and ERIC databases for articles on personal and professional values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 96 publications
4
66
0
Order By: Relevance
“…The identified TCs both confirm findings from prior research and offer novel insights into how we might be able to support trainee development. They confirm previous findings, in that, for each identified TC, we could identify studies supporting their importance in trainee development . When identified and labelled as we have done, they also offer a potentially novel opportunity for supporting trainee development .…”
Section: Discussionsupporting
confidence: 87%
“…The identified TCs both confirm findings from prior research and offer novel insights into how we might be able to support trainee development. They confirm previous findings, in that, for each identified TC, we could identify studies supporting their importance in trainee development . When identified and labelled as we have done, they also offer a potentially novel opportunity for supporting trainee development .…”
Section: Discussionsupporting
confidence: 87%
“…Another interesting finding that clients placed importance on ‘sharing professional values’ correlates with the higher expectations of a more educated, informed veterinary clientele, and affirms the value of the client voice in curricula . On the other hand, it was not unexpected that graduates, veterinarians and academics agreed on the importance of shared values which are internalised with professional socialisation during clinical education and following graduation . However, differences in professional socialisation and values supported by uniprofessional education can create impediments to teamwork and interprofessional collaboration .…”
Section: Discussionmentioning
confidence: 99%
“…The interprofessional literature reports that a respect for diversity is fundamental to effective collaborative teamwork, and requires understanding and respect for the scope and complementarity of each member's role . Differences in values and views on diversity may reflect the impact of a uniprofessional education . A co‐curricular approach to clinical education including a ‘common values framework’ 49,p.258 that is reinforced during VT and veterinary student clinical rotations would help to break down hierarchical barriers that create an impediment to veterinary teamwork …”
Section: Discussionmentioning
confidence: 99%
“…Being chronically sick and having views that are easy to influence may be perceived by dialyzed patients as more beneficial from an overall psychological and medical well-being standpoint [5,6,10]. In fact, it has been shown that the Western style of medicine discourages a patient’s active participation because that participation may be perceived as a hindrance by medical personnel [12]. Additionally, the circumstances of HD are more passive, since hemodialysis is done without the patient’s active involvement.…”
Section: Discussionmentioning
confidence: 99%
“…After all, members of the medical staff are the gatekeepers of a life-saving therapy. On the other hand, lack of patient cooperation with medical treatment results in a perception by medical personnel of the patient as “difficult” and can result in concomitant deterioration due to inadequate compliance with the demands of RRT [5,6,10,12,13]. In the situation of any psychological testing, conformity may bias the result if the participant is answering the questionnaire to please the interviewer and not necessarily to report their actual state of affairs [11,14].…”
Section: Introductionmentioning
confidence: 99%